Monetary Policy Uncertainty and Inflation Expectations - Gabriel Arce-Alfaro; Boris Blagov (Oxford Bulletin of Economics and Statistics, 2022)
Do inflation expectations react to changes in the volatility of monetary policy? They have, but only until the global financial crisis. This paper investigates whether increasing the dispersion of monetary policy shocks, which is interpreted as elevated uncertainty surrounding monetary policy, affects the inflation expectation formation process. Based on US data since the 1980s and a stochastic volatility-in-mean structural VAR model, we find that monetary policy uncertainty reduces both inflation expectations and inflation. However, after the Great Recession this link has disappeared, even when controlling for the Zero Lower Bound.
Keywords: 330